Literasi Pemilihan Cosmetik Halal Bagi Gen Z Sebagai Peluang Bisnis di Era Digital (Studi Kasus Pada Siswi Man 1 Kota Gorontalo) - Dewi Indrayani Hamin; Yayu Isyana Pongoliu (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
.Islam allows decorating, but using cosmetics must be in accordance with Islamic law, starting from the raw materials to the manufacturing process, not excessive, and not endangering the user. Along with global trends, the use of these cosmetic products is increasingly widespread in various parts of the world. Because of the high consumer demand for cosmetics. Cosmetics are a must-have item regardless of age and gender. This is a great opportunity for business people. Meanwhile, millennial consumers are a consumer segment that lives at a time when technological developments are running very rapidly, they are used to using technology and the internet to connect with a very large number of other people on a regular basis, at the same time. This generation has significantly more social network connections than any other generation, they have lots of online friends, and are able to improve their psychological aspects when they can engage with their friends. On the other hand, cosmetics sticking to the face and other parts of the body affect the requirements for the validity of prayer, namely being clean from uncleanness. every Muslim should pay attention and ensure that there is no more impurity on the body. The service activity was carried out in the City of Gorontalo Dulalowo Timur for young female students of MAN 1 Gorontalo. The activity methods used in this service are material, practice, and questions and answers. From this activity it resulted that the understanding and practice of young women regarding halal cosmetic literacy and business opportunities in the digital era in the good category 65% and 35% were quite good categories.